2015
DOI: 10.1002/casp.2262
|View full text |Cite
|
Sign up to set email alerts
|

Re‐building Bridges: Homeless People's Views on the Role of Vocational and Educational Activities in Their Everyday Lives

Abstract: Homeless people face everyday challenges of marginalisation and stigmatisation. Consequently, they can suffer from low self-confidence, selfefficacy and agency. Empirical research in Britain on educational, skill-building and meaningful activities for homeless people principally emphasises the instrumental value of training and learning as a route to employment rather than the impact of activities on homeless people's everyday lives. Theoretical literature suggests that psychosocial benefits related to the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The community as a context for engagement and belonging. Nine themes representing eight studies characterised the community as a rich context for engaging in meaningful activities with others and facilitating belonging [2,4,6,7,30,34,35,37]. Participants reported that they engaged in activities that either strengthened relationships within their families or created "street families."…”
Section: Activity As a Means Of Belongingmentioning
confidence: 99%
See 4 more Smart Citations
“…The community as a context for engagement and belonging. Nine themes representing eight studies characterised the community as a rich context for engaging in meaningful activities with others and facilitating belonging [2,4,6,7,30,34,35,37]. Participants reported that they engaged in activities that either strengthened relationships within their families or created "street families."…”
Section: Activity As a Means Of Belongingmentioning
confidence: 99%
“…Parents living in a family shelter with their children preserved family routines by maintaining schedules that facilitated community connection [4]. The need to negotiate the social contexts of their environments on an ongoing basis, and the isolation that resulted from being excluded from mainstream activities such as employment were identified in two studies as factors leading to a loss of belonging and stigma associated with homelessness [6,7,34]. Participants in one study noted that places once utilised by the general public had been largely coopted by homeless persons, and became important places in which to find and engage in activities of meaning [35].…”
Section: Activity As a Means Of Belongingmentioning
confidence: 99%
See 3 more Smart Citations